Valorisation of cheese whey into single-cell protein by Lactococcus garvieae: dual waste nitrogen supplementation and uncertainty-informed process evaluation - Uzun, Halil Ibrahim; Onlu, Harun (Springer, 2026)
Growing global protein demand necessitates resource-efficient alternatives to conventional production systems. This study developed a waste-based bioprocess framework for converting cheese whey (CW) into single-cell protein (SCP) using lactic acid bacteria within a dual waste-valorisation configuration integrating CW and expired chickpea flour-derived extract. Seven LAB strains were screened in pre-treated CW, and Lactococcus garvieae was selected based on its highest biomass formation in untreated whey (0.441 +/- 0.024 g/L). As CW was nitrogen-limited, supplementation with water-soluble legume extracts significantly enhanced SCP production, with chickpea extract (CE) yielding 1.560 +/- 0.120 g/L at 10 g/L. Among the tested carbon sources, sucrose supported the highest biomass concentration (2.110 +/- 0.105 g/L). Under the selected cultivation conditions (pH 7.0, 37 degrees C), SCP reached 2.314 +/- 0.090 g/L. Although the highest observed biomass concentration occurred at 72 h (2.663 +/- 0.154 g/L), volumetric productivity peaked at 24 h (0.096 g/L & centerdot;h), which was therefore selected as the operational incubation time based on the productivity-time trade-off. Second-order polynomial modelling combined with Delta Method-based uncertainty estimation enabled quantitative differentiation between model-derived stationary points and experimentally justified operating conditions. The integration of expired legume flour as a waste-derived nitrogen source, together with uncertainty-aware response modelling within an OFAT framework, establishes a dual waste-valorisation strategy and a transparent approach for statistically supported process window identification under laboratory-scale constraints. The resulting SCP biomass contained 56.37 +/- 2.75% protein, 2.87 +/- 0.34% lipids, and 10.55 +/- 0.68% ash.
Keywords: Single-Cell Protein; Cheese Whey; Waste Valorisation; Lactic Acid Bacteria; Uncertainty Analysis